Compliance Without Experience? A Task-Based WCAG 2.1 Evaluation of Mobile Banking in Indonesia - Fatin Maetam; Chanifah Indah Ratnasari (Jurnal Pendidikan Informatika (EDUMATIC), 2026)
Mobile banking applications play a central role in digital financial systems; however, accessibility for users with visual impairments remains insufficiently examined in real task contexts. Existing studies primarily emphasize automated and interface-level assessments, with limited attention to interaction processes during task execution. This study evaluates the accessibility of a widely used mobile banking application in Indonesia using a task-based approach based on WCAG 2.1 Level A and AA criteria. An exploratory descriptive case study was conducted on BRImo (version 2.92.0) using Android 13 and TalkBack 16.2.0. The evaluation integrates manual WCAG inspection, automated testing, and screen reader-based interaction testing across three core tasks: login authentication, balance inquiry, and fund transfer. The unit of analysis focuses on interaction steps within task workflows, examined through a triangulation approach comparing structural compliance and interaction-level outcomes. The findings show substantial partial conformance, with over 70% of Level A and nearly 90% of Level AA criteria categorized as “Supports with Exceptions.” However, critical barriers persist in transactional workflows, including missing labels, inconsistent screen reader feedback, and navigation failures that hinder task completion. These results indicate that WCAG conformance alone is insufficient to ensure functional accessibility, highlighting the distinction between structural conformance and experiential task accessibility.